Effect of Mating and Polymorphism Insulin Like growth Factor binding Protein 2 Gene on Body Weight and Heritability of Kampung Chicken - Sudaryati, Sri; Sidadolog, Jafendi Hasoloan Purba; Wihandoyo, Wihandoyo; Artama, W. T. (2015)
Insulin-like growth factor binding protein 2 (IGFBP2) regulates a broad spectrum of biological activities involved in growth, development, and differentiation. Single nucleotide polymorphisms C1032T of IGFBP2 gene was used to genotyped parents and their progenies of Kampung chicken using PCR-RFLP method. Found 3 genotypes that were CC, CT, and TT. Four pairs mating that were CC><CC (1), TT><CT (2), CT><CT (3), and CC><CT (4), were raised to produce their progenies. Then the progenies was raised until 12 week of age and weekly weighed individually. Weekly body weight was analyzed by analyzed one way variance =, heritability and breeding value was analyzed by formula of Falconer and MacKay (1997). The result showed that eventhough the weekly body weight inconcictency in weight gain but progeny of mating 3 and 4 had better body weight than progeny of mating 1 and 2. Weekly body weight heritability was low to high (0.013- 0.681), moderate heritability was on age 2 week (0.446) and high heritability was on age 12 week of age (0.681). breeding values were gain wider with the increasing age. Progeny of mating number 1 and 2 showed slower growth rate than number 3, and the best growth rate was progeny of number 4 at period 8 to 12 week age. It was conclude that IDFBP2 gene was associated with growth and parameter genetic in Kampung chicken.